The CFS Choux Questionnaire: Lisa Heldke, food philosopher - Lisa Heldke (Canadian Food Studies, 2023)
A riff on the well-riffed Proust Questionnaire, the Canadian Food Studies Choux Questionnaire is meant to elicit a tasty and perhaps surprising experience, framed within a seemingly humble exterior. (And yes, some questions have a bit more craquelin than others.) Straightforward on their own, the queries combined start to form a celebratory pyramid of extravagance. How that composite croquembouche is assembled and taken apart, however, is up to the respondents and readers to determine. Respondents are invited to answer as many questions as they choose. The final question posed—What question would you add to this questionnaire?—prompts each respondent to incorporate their own inquisitive biome into the mix, feeding a forever renewed starter culture for future participants.